Strategi Penanaman Karakter Religius Siswa Melalui Pembiasaan Shalat Dhuha Dan Membaca Al-Qur'an di SDN Sendanggayam - Siti Rohmah; Sunan Baedowi; Intan Rahmawati (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
The decline in students’ religious character has contributed to various educational issues, including a rise in bullying and other forms of juvenile delinquency. Strengthening religious character is therefore a fundamental component of the educational process, particularly at the elementary school level. Religious character refers to a spiritual disposition manifested through daily behavior aligned with religious teachings. This study aims to explore the strategies employed in fostering religious character through the habituation of Dhuha prayer and Qur’an recitation at SDN Sendanggayam. It also seeks to identify the supporting and inhibiting factors, along with the efforts made to address existing challenges. Utilizing a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings indicate that the daily implementation of Dhuha prayer and Qur’an recitation effectively cultivates core religious values, including discipline, responsibility, empathy, tolerance, and moral conduct. Key supporting factors include the availability of adequate facilities and infrastructure, as well as active support from the school, teachers, and parents. However, challenges arise from students’ lack of seriousness and limited understanding of Tajweed and the meaning of Qur’anic verses. To overcome these barriers, consistent habituation, targeted religious education, and strong collaboration between the school and parents are essential strategies.